(untitled) (Stavební obzor - Civil Engineering Journal, 2020)
Historic buildings located in areas exposed to dynamic effects caused by natural or technical seismicity are one of the most vulnerable types of structures. Masonry buildings often have timber-ceiling structures with insufficient rigidity and not fully functional system of wall and beam ties, therefore being extremely sensitive to the dynamic effects caused by natural or technical seismicity. Main focus of the article is the outline of possible rehabilitation and restoration design approaches for strengthening of historic buildings in terms of dynamic loads. Brief information about the research performed in the field of masonry vaults’ reinforcement due to the dynamic loading is presented.